Non‐Fluorinated Polymer Composite Proton Exchange Membranes for Fuel Cell Applications – A Review - Esmaeili, Nazila; Gray, Evan MacA; Webb, Colin J. (Chemphyschem, 2019)
The critical component of a proton exchange membrane fuel cell (PEMFC) system is the proton exchange membrane (PEM). Perfluorosulfonic acid membranes such as Nafion are currently used for PEMFCs in industry, despite suffering from reduced proton conductivity due to dehydration at higher temperatures. However, operating at temperatures below 100 °C leads to cathode flooding, catalyst poisoning by CO, and complex system design with higher cost. Research has concentrated on the membrane material and on preparation methods to achieve high proton conductivity, thermal, mechanical and chemical stability, low fuel crossover and lower cost at high temperatures. Non‐fluorinated polymers are a promising alternative. However, improving the efficiency at higher temperatures has necessitated modifications and the inclusion of inorganic materials in a polymer matrix to form a composite membrane can be an approach to reach the target performance, while still reducing costs. This review focuses on recent research in composite PEMs based on non‐fluorinated polymers. Various inorganic fillers incorporated in the PEM structure are reviewed in terms of their properties and the effect on PEM fuel cell performance. The most reliable polymers and fillers with potential for high temperature proton exchange membranes (HTPEMs) are also discussed. Composite organic‐inorganic polymers, consisting of an inorganic material embedded in a non‐fluorinated polymer phase, offer the possibility of an improvement in the performance of PEM fuel cells, currently dominated by perfluorosulfonic acid membranes. This review details recent research in composite PEMs based on non‐fluorinated polymers, including high temperature PEMs.